Mind the GAP: quantifying the breakdown of the linear vibronic coupling Hamiltonian. Issue 10 (23rd February 2023) - Penfold, Thomas J; Eng, Julien
Abstract : The linear vibronic coupling approximation provides an efficient and simple approach to develop a model Hamiltonian. Herein we present a metric to assess its validity. To avoid the breakdown of the linear vibronic coupling approximation, mind the gap. Abstract : Excited state dynamics play a critical role across a broad range of scientific fields. Importantly, the highly non-equilibrium nature of the states generated by photoexcitation means that excited state simulations should usually include an accurate description of the coupled electronic–nuclear motion, which often requires solving the time-dependent Schrödinger equation (TDSE). One of the biggest challenges for these simulations is the requirement to calculate the PES over which the nuclei evolve. An effective approach for addressing this challenge is to use the approximate linear vibronic coupling (LVC) Hamiltonian, which enables a model potential to be parameterised using relatively few quantum chemistry calculations. However, this approach is only valid provided there are no large amplitude motions in the excited state dynamics. In this paper we introduce and deploy a metric, the global anharmonicity parameter (GAP), which can be used to assess the accuracy of an LVC potential. Following its derivation, we illustrate its utility by applying it to three molecules exhibiting different rigidity in their excited states.